Advancing Research for Library and Information Science with Qualitative Secondary Analysis - Bossaler, Jenny; Burns, C.Sean; VanScoy, Amy (Qualitative and Quantitative Methods in Libraries; Vol 5 No 3 (2016): September 2016 Issue, 2017)
This paper presents the results of a study utilizing a seldom-used method in Library and Information Science (LIS): Qualitative Secondary Analysis. The data is drawn from two phenomenological studies about experiences of Reference and Information Services (RIS) librarians. We discuss how we repurposed the interview data in this study, and also the strengths, weaknesses, and wider applications of the method across LIS.